National Microbiological Laboratory Reporting Service - Bulletin 12. 3-16 June 1977 - whole issue - No author listed (Communicable Diseases Intelligence, 1977)
Whole-issue pdf, comprising: Article Herpes simplex. [modifications of the descriptions used in Bulletin Tables] Viruses in immunosuppressed patients. "Readers might be interested in the list below, which was compiled from a manual search of records for Periods 10 and 11, to give an idea of which patients were having specimens referred. [continues...]" National Microbiological Laboratory Reporting Service - Period 12 3-16 June 1977